High-impermeability surgical operation sheet and preparation method thereof

By adopting the collaborative process of linear low-density polyethylene, metallocene polyethylene, polymer polyethylene and sheet-like materials in surgical sheet laying, a composite anti-seepage film is formed and hot-pressed composite with non-woven fabrics, the problem of reducing anti-seepage effect of traditional sheet laying under high anti-seepage requirements is solved, and the combination of high anti-seepage and good mechanical properties is achieved.

CN119898043APending Publication Date: 2025-04-29JIANGSU AISHELUN MEDICAL TECH GRP CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510377237.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-28
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The anti-seepage effect of traditional surgical PE membranes may be greatly reduced when faced with prolonged fluid erosion, especially in surgeries with high sterility and anti-seepage requirements, such as neurosurgery and cardiac surgery.

Method used

The composite anti-seepage film is formed by mixing linear low-density polyethylene, metallocene polyethylene, polymer polyethylene and sheet-like materials, and melt blending and casting processes are performed in a twin-screw extruder and casting machine. Then the non-woven fabric and the composite anti-seepage film were heat-pressed to prepare a high anti-seepage surgical sheet.

Benefits of technology

It significantly improves the anti-seepage and mechanical properties of the surgical sheet, can meet the surgical needs of high anti-seepage standards and structural stability, and reduces the risk of infection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119898043A_ABST
    Figure CN119898043A_ABST
Patent Text Reader

Abstract

The invention discloses a high-impermeability surgical drape and a preparation method thereof, and relates to the field of layered products, the preparation method comprises the following steps: S1, mixing mLLDPE, mPE, macromolecular polyethylene and a sheet material to obtain a mixed material; s2, adding the mixture into a double-screw extruder, carrying out melt blending, and extruding a molten material flow; s3, conveying to a die head of a casting machine to form a uniform thin film, performing ultrasonic assistance, and cutting to obtain a composite impermeable film; s4, the non-woven fabric and the composite impermeable film are subjected to hot-pressing compounding, and the surgical operation sheet is obtained. Through cooperation of materials and optimization of proportioning process parameters, and in combination with melt flow direction control and ultrasonic assistance in a tape casting process, the uniformity and compactness of the surgical drape are remarkably improved, and the surgical drape shows excellent anti-seepage performance and also has good mechanical properties; the requirements of high anti-seepage standards and stable-structure surgeries such as neurosurgery and cardiac surgeries are met, and the infection risk is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of layered products, and in particular to a highly impermeable surgical drape and a preparation method thereof. Background Art

[0002] In surgical operations, drapes are an important part of ensuring that the surgical area is sterile, dry, and safe. Drapes not only isolate the surgical area from the outside environment and reduce the chance of contamination, but also protect the patient's skin from irritation and damage by disinfectants, thereby reducing the risk of postoperative infection. With the continuous advancement of medical technology, the materials and structures of surgical drapes are also constantly being updated and optimized to meet higher standards of surgical safety.

[0003] Traditional surgical drapes are mainly composed of non-woven fabrics and PE films. As the base material, non-woven fabrics can fit the patient's skin and have good air permeability and softness. The polyethylene (PE) film is used as an impermeable layer. With its low permeability, it effectively blocks the penetration of gas and water vapor and prevents liquid leakage during surgery. However, although the PE film provides an impermeable effect to a certain extent, its impermeability performance is relatively limited, especially in some special surgeries, such as neurosurgery and cardiac surgery, where the surgical area requires higher sterility and impermeability standards. The PE film impermeable layer of traditional surgical drapes may greatly reduce its impermeability effect when facing long-term liquid erosion.

[0004] Therefore, it is necessary to improve the deficiencies in the prior art to solve the above problems. Summary of the invention

[0005] The invention overcomes the shortcomings of the prior art and provides a highly impermeable surgical drape and a preparation method thereof.

[0006] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing a highly impermeable surgical drape, comprising the following steps: S1, mixing linear low-density polyethylene, metallocene polyethylene, high-molecular polyethylene, and sheet materials to obtain a mixed material; S2, adding the mixed material into a twin-screw extruder, melt blending, and extruding a molten material stream; S3, conveying the molten material flow to the die head of the casting machine, forming a uniform film through a scraper, controlling the casting speed and the temperature of the cooling roller, and performing ultrasonic assistance to cut and obtain a composite anti-seepage membrane; S4. The nonwoven fabric and the composite anti-seepage membrane are laminated by hot pressing to obtain a surgical drape.

[0007] In a preferred embodiment of the present invention, in step S1, the mass ratio of the linear low-density polyethylene, metallocene polyethylene, high-molecular polyethylene and sheet material is 4-6:2-3:1-2:0.5-1.5.

[0008] In a preferred embodiment of the present invention, in the step S1, the polymer polyethylene is one of high-density polyethylene or ultra-high molecular weight polyethylene; the sheet material is one of mica sheets or boron nitride nanosheets, the particle size of the mica sheets is 5~50 μm, and the particle size of the boron nitride nanosheets is 50~100 nm.

[0009] In a preferred embodiment of the present invention, in the step S2, the melt temperature of the twin-screw extruder is 180-220° C., and the screw speed is 100-300 rpm.

[0010] In a preferred embodiment of the present invention, in the step S3, the die head temperature of the casting machine is 200-230°C, the casting speed is 5-10 m / min, and the cooling roller temperature is 20-40°C.

[0011] In a preferred embodiment of the present invention, in the step S3, during the casting process, the flow direction of the molten material flow is parallel to the film surface.

[0012] In a preferred embodiment of the present invention, in step S3, the frequency of the ultrasound assistance is 20-40 kHz, and the power is 10-30 W / cm 2 , time is 1~5 s, and the ultrasonic probe is located at the die entrance or melt flow channel of the casting machine.

[0013] In a preferred embodiment of the present invention, in the step S4, the temperature of the hot pressing composite is 80-120° C., the pressure is 0.5-1 MPa, and the time is 5-10 s.

[0014] The present invention provides a high-impermeability surgical drape, which is obtained by using the preparation method of the high-impermeability surgical drape as described in any one of the above.

[0015] In a preferred embodiment of the present invention, the surgical drape comprises a skin-friendly layer made of a non-woven fabric material and a composite impermeable layer made of a composite impermeable membrane, wherein the thickness of the skin-friendly layer is 0.08-0.15 mm, and the thickness of the composite impermeable layer is 0.03-0.08 mm. The present invention solves the defects existing in the background technology and has the following beneficial effects: The present invention provides a highly impermeable surgical drape and a preparation method thereof. Through the synergy of materials and the optimization of the proportioning process parameters, combined with the melt flow direction control and ultrasonic assistance in the casting process, the short-chain branched mLLDPE and the long-chain branched mPE and the low crystallinity region of HDPE are intertwined, so that the crystalline structure of the entire film material is more complex and dense, and the sheet material extends the diffusion path of water and oxygen molecules, thereby significantly improving the uniformity and density of the surgical drape, showing excellent impermeability, and having good mechanical properties, meeting the high impermeability standards and structural stability requirements of operations such as neurosurgery and cardiac surgery, and reducing the risk of infection.

[0016] In the present invention, mLLDPE is mainly linear in structure, with regular molecular chain arrangement and high crystallinity. During the polymerization process, ethylene is copolymerized with a small amount of high-grade α-olefin to form linear molecular chains with short branches, which can improve the overall mechanical properties. At the same time, the crystalline region formed by the regular molecular chain arrangement is more compact, which can effectively reduce the free volume inside the material, thereby preventing the penetration of liquids and gases. At the same time, the mPE molecular chains are regularly arranged, with high crystallinity, and the formed crystal regions are more compact. The presence of long branches increases the flexibility and ductility of the molecular chains, so that the film is not easy to break when subjected to external forces, further improving the anti-permeability performance.

[0017] In the present invention, an appropriate amount of mica sheets can form an optimal intermolecular interaction force, and the horizontal orientation of the mica sheets is achieved through the shear force of the casting process. The horizontally arranged mica sheets form a multi-layer barrier parallel to the surface in the film, forming an efficient barrier network, forcing water molecules or oxygen molecules to bypass the sheet layer before penetrating the film. The formed maze effect makes the molecular diffusion path length greater than the actual thickness of the film, thereby further improving the anti-permeability performance of the film.

[0018] In the present invention, ultrasonic assistance is performed during the casting process, and its ultrasonic cavitation effect can break up mica agglomerates, prompting them to be peeled off into a single layer or thin sheet structure, reducing agglomeration caused by molecular chain entanglement, and improving dispersion uniformity. At the same time, in the melt, ultrasonic vibration induces the formation of a shear flow field and micro-eddies, which can make the mica sheets further arranged along the flow field direction, and promote the polar interaction between the polymer molecular chains and the hydroxyl groups on the surface of the mica sheets, enhance the interface bonding, and make the mica sheets easier to approach the horizontal direction, thereby further realizing the uniform dispersion and horizontal orientation of the mica sheets, and finally forming a dense, highly oriented composite structure, and improving its anti-seepage and mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work. Figure 1 It is a flow chart of a method for preparing a highly impermeable surgical drape according to a preferred embodiment of the present invention; Figure 2 It is a schematic diagram of the peeling structure of the skin-friendly layer and the composite anti-seepage layer of the surgical drape of the present invention; In the figure: 1. Skin-friendly layer; 2. Composite anti-seepage layer. DETAILED DESCRIPTION

[0020] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.

[0022] It should be noted that the raw materials, equipment and reagents used in the present invention can be purchased from the market or obtained by the preparation method of the existing technology; among them, linear low-density polyethylene is purchased from Shanghai Oushuo Plastic Co., Ltd. with the brand SP0540; metallocene polyethylene is purchased from Dongguan Su Ming Plastic Raw Materials Co., Ltd. with the brand 2018MA; high-density polyethylene is purchased from Dongguan Shangpin New Material Technology Co., Ltd. with the brand E204; ultra-high molecular weight polyethylene is purchased from Zhejiang Jiuding Chemical Materials Co., Ltd. with the brand U-PE200-Ⅱ.

[0023] like Figure 1 As shown, a method for preparing a highly impermeable surgical drape comprises the following steps: S1, mixing linear low-density polyethylene (mLLDPE), metallocene polyethylene (mPE), polymer polyethylene, and sheet material to obtain a mixed material; S2, adding the mixed material into a twin-screw extruder, melt blending, and extruding a molten material stream; S3, conveying the molten material flow to the die head of the casting machine, forming a uniform film through a scraper, controlling the casting speed and the temperature of the cooling roller, and performing ultrasonic assistance to cut and obtain a composite anti-seepage membrane; S4. The nonwoven fabric and the composite anti-seepage membrane are laminated by hot pressing to obtain a surgical drape.

[0024] In some specific embodiments, in step S1, the mass ratio of linear low-density polyethylene, metallocene polyethylene, high-molecular polyethylene and sheet material is 4-6:2-3:1-2:0.5-1.5.

[0025] In some specific embodiments, in step S1, the polymer polyethylene is one of high-density polyethylene (HDPE) or ultra-high molecular weight polyethylene (UHMWPE); the sheet material is one of mica sheets or boron nitride nanosheets (BNNS), the particle size of the mica sheets is 5~50 μm, and the particle size of the boron nitride nanosheets is 50~100 nm.

[0026] In some specific embodiments, in step S2, the melt temperature of the twin-screw extruder is 180-220° C., and the screw speed is 100-300 rpm.

[0027] In some specific embodiments, in step S3, the die temperature of the casting machine is 200-230°C, the casting speed is 5-10 m / min, and the cooling roller temperature is 20-40°C.

[0028] In some specific embodiments, in step S3, during the casting process, the flow direction of the molten material stream is parallel to the film surface.

[0029] In some specific embodiments, in step S3, the frequency of ultrasound assistance is 20-40 kHz and the power is 10-30 W / cm 2 , time is 1~5 s, and the ultrasonic probe is located at the die entrance or melt flow channel of the casting machine.

[0030] In some specific embodiments, in step S4, the temperature of the hot pressing composite is 80-120° C., the pressure is 0.5-1 MPa, and the time is 5-10 s.

[0031] like Figure 2 As shown, the present invention provides a high impermeability surgical drape, which is obtained by using any of the above-mentioned methods for preparing a high impermeability surgical drape.

[0032] In some specific embodiments, the surgical drape includes a skin-friendly layer 1 made of a non-woven fabric material, and a composite impermeable layer 2 made of a composite impermeable membrane, the skin-friendly layer 1 has a thickness of 0.08-0.15 mm, and the composite impermeable layer 2 has a thickness of 0.03-0.08 mm. Example 1

[0033] A method for preparing a highly impermeable surgical drape comprises the following steps: S1, mixing mLLDPE, mPE, HDPE, and mica flakes with a particle size of 30 μm in a mass ratio of 5:2.5:1:1 to obtain a mixed material; S2, adding the mixed material into a twin-screw extruder, melt-blending at a melt temperature of 200° C. and a screw speed of 200 rpm, and extruding a molten material stream; S3, the molten material flow is conveyed to the die head of the casting machine, and a uniform film is formed by a scraper. The die head temperature is controlled to be 210 ℃, the casting speed is 8 m / min, and the cooling roller temperature is 30 ℃. At the same time, during the casting process, the flow direction of the molten material flow is ensured to be parallel to the film surface. During the process, the ultrasonic probe is located in the melt flow channel, and the frequency is 30 kHz, 18 W / cm 2 The composite anti-seepage membrane with a thickness of 0.08 mm was obtained by cutting with the power of 1000 nm and ultrasonic assistance for 4 s. S4. The non-woven fabric with a thickness of 0.13 mm and the composite anti-seepage membrane were hot-pressed at a pressure of 1 MPa and a temperature of 90°C for 7 s to obtain a surgical drape with a thickness of 0.21 mm. Example 2

[0034] This embodiment is substantially the same as the embodiment 1, except that: Step S1 is: mLLDPE, mPE, HDPE in a mass ratio of 5:2.5:1:1 are mixed with BNNS having a particle size of 80 nm to obtain a mixed material. Example 3

[0035] This embodiment is basically the same as the embodiment 1, except that: Step S1 is: mixing mLLDPE, mPE, HDPE in a mass ratio of 6:2:2:0.5 with mica flakes with a particle size of 30 μm to obtain a mixed material. Example 4

[0036] This embodiment is basically the same as the embodiment 1, except that: Step S1 is: mixing mLLDPE, mPE, HDPE in a mass ratio of 6:3:2:1.5 with mica flakes with a particle size of 30 μm to obtain a mixed material. Example 5

[0037] This embodiment is basically the same as embodiment 1, except that: step S3 is: the molten material flow is conveyed to the die head of the casting machine, and a uniform film is formed by a scraper, the die head temperature is controlled to be 210°C, the casting speed is 8 m / min, and the cooling roller temperature is 30°C. At the same time, during the casting process, the flow direction of the molten material flow is ensured to be parallel to the film surface, and the ultrasonic probe is located in the melt flow channel at a frequency of 30 kHz and 18 W / cm 2 The composite anti-seepage membrane was cut with ultrasonic assistance for 5 s. Example 6

[0038] This embodiment is basically the same as embodiment 1, except that: step S3 is: the molten material flow is conveyed to the die head of the casting machine, and a uniform film is formed by a scraper, the die head temperature is controlled to be 210°C, the casting speed is 8 m / min, and the cooling roller temperature is 30°C. At the same time, during the casting process, the flow direction of the molten material flow is ensured to be parallel to the film surface, and the ultrasonic probe is located in the melt flow channel at a frequency of 30 kHz and 18 W / cm 2 The power was 1 s and ultrasonic assistance was used to cut the composite anti-seepage membrane.

[0039] Performance testing: The surgical drapes obtained in Examples 1-6 were tested for anti-seepage performance and mechanical properties, and the results are shown in Table 1.

[0040] Anti-permeability performance: With reference to GB / T 21529-2008 "Determination of water vapor transmission rate of plastic films and sheets", the water vapor transmission rate test was carried out at 38 ℃ and 90% relative humidity using the W3 / 330 water vapor transmission rate test system; with reference to GB / T 1038.1-2022 "Test method for gas permeability of plastic film and sheet", the oxygen transmission rate test was carried out at 23 ℃ and 0% relative humidity using the VAC-V2 differential pressure gas permeometer; wherein, the water vapor transmission coefficient (WVTC) and the oxygen transmission coefficient (OTC) are obtained by multiplying the water vapor transmission rate and the oxygen transmission rate by the thickness, respectively.

[0041] Mechanical properties: refer to GB / T 1040.3-2006 "Determination of tensile properties of plastics" to carry out tensile strength and elongation at break tests.

[0042] Table 1: Tests on the impermeability and mechanical properties of surgical drapes of Examples 1-6

[0043] As shown in Table 1: Examples 1-6 of the present invention all demonstrate good anti-seepage performance and mechanical properties. Among them, in terms of anti-seepage performance, Example 1 has a water vapor transmission coefficient WVTC of 1.6×10 2g·μm / (m 2 ·d), oxygen permeability coefficient OTC is 1.1×10 -3 cm 3 ·μm / (m 2 ·d·Pa) and mechanical properties: the tensile strength is 25.6 MPa, and the elongation at break is 726%, which shows excellent anti-seepage performance and good mechanical properties, meeting the surgical requirements of high anti-seepage standards and structural stability such as neurosurgery and cardiac surgery.

[0044] In summary, the present invention achieves the synergy of mLLDPE, mPE, HDPE and sheet materials (mica sheets / boron nitride nanosheets), as well as the optimization of the ratio and process parameters, combined with the melt flow direction control and ultrasonic assistance in the casting process. The short-chain branched mLLDPE and the low crystallinity regions of the long-chain branched mPE and HDPE are intertwined, making the crystal structure of the entire film material more complex and dense, reducing the pores and channels inside the material, effectively preventing the penetration of liquids and gases, and increasing the flexibility and ductility of the molecular chain, so that the film can better disperse stress when subjected to external force, reducing film rupture caused by stress concentration, and the sheet material is horizontally oriented through the casting shear force to form a maze effect, extending the diffusion path of water and oxygen molecules, thereby significantly improving the uniformity and density of the surgical drape, meeting the high anti-seepage requirements of high-standard surgery, and reducing the risk of infection.

[0045] In order to further make the purpose and effect of the present invention simple and easy to understand, the present invention is further described in conjunction with the following specific comparative examples.

[0046] Comparative Example 1 The commercially available surgical drape has a thickness of 0.2 mm and is composed of a surface non-woven fabric and an impermeable PE film.

[0047] Comparative Example 2 This comparative example is substantially the same as Example 1, except that: no mLLDPE is present, and step S1 is: mPE, HDPE, and mica flakes with a particle size of 30 μm in a mass ratio of 2.5:1:1 are mixed to obtain a mixed material.

[0048] Comparative Example 3 This comparative example is substantially the same as Example 1, except that: no mPE is present, and step S1 is: mLLDPE, HDPE, and mica flakes with a particle size of 30 μm in a mass ratio of 5:1:1 are mixed to obtain a mixed material.

[0049] Comparative Example 4 This comparative example is basically the same as Example 1, except that: there is no mica sheet, and step S1 is: mixing mLLDPE, mPE, and HDPE in a mass ratio of 5:2.5:1 to obtain a mixed material.

[0050] Comparative Example 5 This comparative example is basically the same as Example 1, except that the amount of mica flakes used is different. Step S1 is: mLLDPE, mPE, HDPE, and mica flakes with a particle size of 30 μm in a mass ratio of 5:2.5:1:0.3 are mixed to obtain a mixed material.

[0051] Comparative Example 6 This comparative example is basically the same as Example 1, except that the amount of mica flakes used is different. Step S1 is: mLLDPE, mPE, HDPE, and mica flakes with a particle size of 30 μm in a mass ratio of 5:2.5:1:1.7 are mixed to obtain a mixed material.

[0052] Comparative Example 7 This comparative example is basically the same as Example 1, except that: during the casting process, there is no control of the flow direction of the molten material flow, and the step of S3 is: the molten material flow is transported to the die head of the casting machine, and a uniform film is formed by a scraper, the die head temperature is controlled to be 210 ° C, the casting speed is 8 m / min, the cooling roller temperature is 30 ° C, and during the casting process, the ultrasonic probe is located in the melt flow channel, and the frequency is 30 kHz, 18 W / cm 2 The power was 200 W and the ultrasonic-assisted method was used for 4 s to cut the composite anti-seepage membrane with a thickness of 0.08 mm.

[0053] Comparative Example 8 This comparative example is basically the same as Example 1, except that: during the casting process, there is no ultrasonic assistance, and the step of S3 is: conveying the molten material flow to the die head of the casting machine, forming a uniform film by a scraper, controlling the die head temperature to 210°C, the casting speed to 8 m / min, and the cooling roller temperature to 30°C. At the same time, during the casting process, ensure that the flow direction of the molten material flow is parallel to the film surface, and cut to obtain a composite anti-seepage membrane with a thickness of 0.08 mm.

[0054] Comparative Example 9 This comparative example is basically the same as Example 1, except that the ultrasonic assistance time is different, and the step of S3 is: the molten material flow is transported to the die head of the casting machine, and a uniform film is formed by a scraper, and the die head temperature is controlled to be 210 ° C, the casting speed is 8 m / min, and the cooling roller temperature is 30 ° C. At the same time, during the casting process, the flow direction of the molten material flow is ensured to be parallel to the film surface, and the ultrasonic probe is located in the melt flow channel during the process, and the frequency is 30 kHz, 18 W / cm 2 The power was 0.08 mm and the composite anti-seepage membrane was cut with ultrasonic assistance for 7 s.

[0055] Performance testing: The surgical drapes obtained in Comparative Examples 1-9 were tested for anti-seepage performance and mechanical properties in turn using the performance testing methods in Examples 1-6. The results are shown in Table 2.

[0056] Table 2: Anti-seepage and mechanical properties test of surgical drapes of comparative examples 1-9

[0057] As shown in Table 2: By comparing Example 1 with Comparative Example 1, it can be seen that Comparative Example 1 uses traditional surgical drape materials, and its anti-seepage performance and mechanical properties are significantly lower than those of Example 1. The traditional PE film only contains non-woven fabrics and ordinary PE anti-seepage layers. The PE film is used as an anti-seepage layer, and its molecular structure is relatively simple, the molecular chain branching degree is low, the crystallinity is insufficient, and the free volume is large, resulting in a short permeation path and difficulty in effectively blocking the penetration of gas and moisture. The present invention forms a dense crystalline area and a mica barrier through the synergistic effect of the composite material, and the barrier performance is significantly improved, and it also has good mechanical properties.

[0058] By comparing Example 1 with Comparative Examples 2 and 3, it can be seen that Comparative Example 2 does not have mLLDPE, resulting in loose molecular chain arrangement, decreased density of the crystalline region, and WVTC and OTC increased to 2.5×10 2 and 2.1×10 -3 , the mechanical properties decrease due to the reduced stress dispersion ability. Comparative Example 3 does not have mPE. The lack of long-chain branched mPE leads to insufficient flexibility of the molecular chain and weak interface bonding. Both of them slightly decrease in anti-seepage and mechanical properties. The proportion of amorphous areas increases, and the free volume increases. mLLDPE is mainly linear in structure, with regular molecular chains and high crystallinity. During the polymerization process, ethylene copolymerizes with a small amount of high-grade α-olefins (such as butene-1, hexene-1, octene-1, etc.) to form linear molecular chains with short branches, which can improve the overall mechanical properties. At the same time, the crystalline area formed by its regular molecular chain arrangement is more compact, which can effectively reduce the free volume inside the material, thereby preventing the penetration of liquids and gases. The mPE molecular chains are arranged regularly, with high crystallinity, and the formed crystalline areas are more compact. The presence of long chain branches increases the flexibility and ductility of the molecular chains, making the film less likely to break when subjected to external forces, further improving the anti-seepage performance.

[0059] By comparing Example 1 with Comparative Example 4, it can be seen that the absence of mica flakes leads to the failure of the physical barrier, and the permeation path has no extension effect only by relying on the PE crystal structure, and its WVTC rises to 3.0×10 2 , OTC up to 2.5×10 -3The mechanical properties are slightly reduced due to the lack of sheet reinforcement. The addition of mica sheets can significantly enhance the interaction between molecules, form a denser molecular structure, and improve the strength of the membrane material to a certain extent. Therefore, the lack of mica sheets leads to a double decline in anti-seepage performance and mechanical properties.

[0060] By comparing Example 1 with Comparative Examples 5 and 6, it can be seen that an appropriate amount of mica flakes can form the best intermolecular interaction force. Too few mica flakes will lead to discontinuous barriers and fail to fully exert their reinforcing effect. Too many mica flakes will destroy the continuity of the matrix, unevenly bond the molecular chains to the mica interface, and easily destroy the PE continuous phase, forming stress concentration points, resulting in inferior barrier properties and mechanical properties to those of Example 1.

[0061] By comparing Example 1 with Comparative Example 7, it can be learned that the disordered melt flow causes the mica flake crystal arrangement orientation to be chaotic, the barrier layer to be disordered, the maze effect to be weakened, and the horizontal orientation of the mica flakes is achieved through the shear force of the casting process. The horizontally arranged mica flakes form a multi-layer barrier parallel to the surface in the film, forming an efficient barrier network, forcing water molecules or oxygen molecules to bypass the sheet layer before penetrating the film. The formed maze effect makes the molecular diffusion path length greater than the actual thickness of the film, thereby further improving the anti-permeability performance of the film.

[0062] By comparing Example 1 with Comparative Example 8, it can be learned that by performing ultrasonic assistance during the casting process, the ultrasonic cavitation effect can break up the mica agglomerates and promote their peeling into a single layer or thin sheet structure, reduce the agglomeration caused by the entanglement of molecular chains, and improve the dispersion uniformity. At the same time, in the melt, ultrasonic vibration induces the formation of shear flow fields and micro-eddies, which can make the mica sheets further arranged along the flow field direction, and promote the polar interaction between the polymer molecular chains and the hydroxyl groups on the surface of the mica sheets, enhance the interface bonding, and make the mica sheets easier to approach the horizontal direction, thereby further realizing the uniform dispersion and horizontal orientation of the mica sheets, and finally forming a dense, highly oriented composite structure, improving its anti-seepage and mechanical properties. ‌‌‌ By comparing Example 1 with Comparative Example 9, it can be learned that appropriate ultrasonic assistance can enhance the anti-seepage and mechanical properties of surgical drapes. Ultrasonic cavitation that lasts too long can easily cause the interfacial hydrogen bonds between the mica sheets and the polymer matrix to be repeatedly sheared and eventually broken, thereby reducing the interfacial bonding strength and forming a permeation channel. When the vibration energy exceeds the relaxation threshold of the molecular chain, the oriented mica sheets will be angularly offset due to the elastic retraction of the polymer melt, forming a disordered stack, thereby causing a certain decline in the performance of the surgical drape.

[0063] The above is based on the ideal embodiment of the present invention. Through the above description, it is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic characteristics of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is limited by the attached claims rather than the above description, and it is intended to include all changes within the meaning and scope of the equivalent elements of the claims. Any figure mark in the claims should not be regarded as limiting the claims involved.

[0064] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing a highly impermeable surgical drape, characterized in that: The following steps are involved: S1, mixing linear low-density polyethylene, metallocene polyethylene, high-molecular polyethylene, and sheet materials to obtain a mixed material; S2, adding the mixed material into a twin-screw extruder, melt blending, and extruding a molten material stream; S3, conveying the molten material flow to the die head of the casting machine, forming a uniform film through a scraper, controlling the casting speed and the temperature of the cooling roller, and performing ultrasonic assistance to cut and obtain a composite anti-seepage membrane; S4. The nonwoven fabric and the composite anti-seepage membrane are laminated by hot pressing to obtain a surgical drape.

2. The method for preparing a highly impermeable surgical drape according to claim 1, characterized in that: In the step S1, the mass ratio of the linear low-density polyethylene, the metallocene polyethylene, the high-molecular polyethylene and the sheet material is 4-6:2-3:1-2:0.5-1.

5.

3. The method for preparing a highly impermeable surgical drape according to claim 1, characterized in that: In the step S1, the polymer polyethylene is one of high-density polyethylene and ultra-high molecular weight polyethylene; the sheet material is one of mica sheets and boron nitride nanosheets, the particle size of the mica sheets is 5-50 μm, and the particle size of the boron nitride nanosheets is 50-100 nm.

4. The method for preparing a highly impermeable surgical drape according to claim 1, characterized in that: In the step S2, the melt temperature of the twin-screw extruder is 180-220° C., and the screw speed is 100-300 rpm.

5. The method for preparing a highly impermeable surgical drape according to claim 1, characterized in that: In the step S3, the die head temperature of the casting machine is 200-230°C, the casting speed is 5-10 m / min, and the cooling roller temperature is 20-40°C.

6. The method for preparing a highly impermeable surgical drape according to claim 1, characterized in that: In the step S3, during the casting process, the flow direction of the molten material flow is parallel to the film surface.

7. The method for preparing a highly impermeable surgical drape according to claim 1, characterized in that: In step S3, the frequency of the ultrasound assistance is 20-40 kHz, and the power is 10-30 W / cm 2 , time is 1~5 s, and the ultrasonic probe is located at the die entrance or melt flow channel of the casting machine.

8. The method for preparing a highly impermeable surgical drape according to claim 1, characterized in that: In the step S4, the temperature of the hot pressing composite is 80-120° C., the pressure is 0.5-1 MPa, and the time is 5-10 s.

9. A highly impermeable surgical drape, characterized in that: The method for preparing a highly impermeable surgical drape is used as described in any one of claims 1 to 8.

10. The high impermeability surgical drape according to claim 9, characterized in that: The surgical drape comprises a skin-friendly layer made of a non-woven fabric material and a composite anti-seepage layer made of a composite anti-seepage membrane, the thickness of the skin-friendly layer is 0.08-0.15 mm, and the thickness of the composite anti-seepage layer is 0.03-0.08 mm.

Citation Information

Patent Citations

  • High-strength PE cast film and preparation method thereof

    CN112194839A

  • Single-material barrier protection composite material and isolation gown made of same

    CN115387032A

  • Medicinal antibacterial polyethylene barrier film and preparation method thereof

    CN118956050A